2007
DOI: 10.1002/jor.20361
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical bone mass in mice with inactivation of interleukin‐4 and interleukin‐13

Abstract: The aim of the present study was to study the in vivo role of IL-4 and IL-13 on bone metabolism. The skeletal phenotypes of male and female IL-13(n ¼ 7þ7), and WT (n ¼ 7þ7) mice were compared. Analysis was made at 6 weeks of age (juvenile) by pQCT, and at 20 weeks of age (adult) by pQCT, biomechanical testing, and by S-IGF-1 and SOsteocalcin measurements. The skeletal phenotype was affected only in adult male IL-4mice. These animals displayed a reduction in cortical bone mineral content (BMC) of both the tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Neo‐osteogenesis, multiple sinus surgeries, and eosinophilic rhinosinusitis may share a common endpoint of recalcitrant disease secondary to poorly controlled inflammation. The concept of interleukin 4 (IL4) and IL13 playing an important role in the complex process of neo‐osteogenesis has been proposed in several studies . Neo‐osteogenesis may be merely an endpoint of a chronic process of T helper 2 (Th2) inflammation, driven by IL4 and IL13.…”
Section: Discussionmentioning
confidence: 99%
“…Neo‐osteogenesis, multiple sinus surgeries, and eosinophilic rhinosinusitis may share a common endpoint of recalcitrant disease secondary to poorly controlled inflammation. The concept of interleukin 4 (IL4) and IL13 playing an important role in the complex process of neo‐osteogenesis has been proposed in several studies . Neo‐osteogenesis may be merely an endpoint of a chronic process of T helper 2 (Th2) inflammation, driven by IL4 and IL13.…”
Section: Discussionmentioning
confidence: 99%
“…The T-helper 2 (Th2) cytokines IL-4, IL-10, and IL-13 belong to the family of anti-inflammatory cytokines that play an important role in inflammatory and immune responses [ 16 , 17 ]. In particular, IL-4 inhibits bone resorption [ 18 , 19 ], and its depletion can lead to a reduction in cortical bone mass in adult male mice [ 20 ]. In addition, IL-4 enhances osteogenesis by cocultures of proinflammatory M1 macrophages with preosteoblastic MC3T3 cells by modulating the M1 macrophage phenotype towards M2 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found recently that there was a selective reduction of cortical bone mass in adult male mice depeleted of these Th2-related anti-inflammatory cytokines (Silfversward et al 2007). This finding prompted us to perform the present investigation, which was designed to investigate the role of IL-4 and IL-13 in bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, excessive expression of IL-4 in transgenic mice results in a low-turnover osteoporosis (Lewis et al 1993). Recently, we found that depletion of IL-4 and IL-13 led to an isolated reduction in cortical bone mass in adult male mice (Silfversward et al 2007). As this indicates that IL-4 and IL-13 may possibly have a role in bone modeling, we considered that it would be of interest to study their effects in other events associated with bone formation, such as fracture healing and heterotopic bone formation.…”
mentioning
confidence: 99%